EKSPLORASI STRATEGI PEMASARAN BERBASIS INTEGRASI SWOT DAN BUSINESS MODEL CANVAS PADA KEDAI KOPI BEDREK UNTUK MENINGKATKAN KEUNGGULAN BERSAING - Johanda F, Petrus Damianus; Rukin, Rukin; Sudarsono, Heri (JEB17 : Jurnal Ekonomi dan Bisnis, 2025)
This study aims to explore the marketing strategies of Kedai Kopi Bedrek by integrating SWOT analysis and the Business Model Canvas (BMC) to strengthen competitive advantage in the increasingly dynamic coffee industry. The research employed a descriptive qualitative approach, with data collected through observation, interviews, and documentation involving the café’s management and customers. SWOT analysis was applied to identify internal strengths and weaknesses, as well as external opportunities and threats, while the BMC framework was utilized to map the nine essential components of the business model, including value propositions, customer segments, distribution channels, and customer relationships. The findings reveal that Kedai Kopi Bedrek’s strengths lie in its differentiated products rooted in local wisdom, strategic location, and a loyal customer community. However, limitations were found in promotional resources and human capital capacity. Major opportunities arise from the growing coffee consumption trend among younger generations, the rapid advancement of digital technology, and potential collaboration with creative communities. On the other hand, threats include intense competition from modern coffee shops, fluctuating raw material prices, and shifting consumer preferences. The integration of SWOT and BMC led to several priority strategies, such as strengthening branding based on local values, optimizing digital marketing, diversifying menu offerings, and developing strategic partnerships with local businesses. These findings emphasize that a marketing strategy derived from the integration of SWOT and BMC provides a more comprehensive direction to enhance competitiveness and ensure business sustainability for Kedai Kopi Bedrek